On-line supercritical fluid extraction-high performance liquid chromatography for the analysis of polycyclic aromatic hydrocarbons - 561482 Umi Kalthom Ahmad; Norizah M. Salleh; Seminar Hyphenated Techniques in Chromagraphy and Hyphenated Chromatographic Analyzers : (1996 : Brudges, Belgium)
42